EVOLUTION OF CHAKA SALT LAKE DURING THE LAST 16000 YEARS AND ITS RESPONSE TO CLIMATIC CHANGE - Liu X.; Wang Y.; Shen J.; Wang S.; Yang B. (My University, 2007)
Evaporate minerals, carbonate, detrital minerals, and total organic carbon (TOC) and total nitrogen (TN) in detrital sediments from core CKL-2004 in Chaka salt lake, are used to reconstruct the evolution of the lake during the last 16000 years. The lakewater was fresh between 16000 and 11700 cal. a BP. The B lling-Aller d warm event and Younger Dryas cold event respectively between 13900 and 12400 cal. a BP, and between 12400 and 11700 cal. a BP, were recorded. The lake began to shrink between 11700 and 5900 cal. a BP. A short and obvious desalt period occurred between 5900 and 5250 cal. a BP. The lake shrank fast after 5250 cal. a BP(?), especially after 2300 cal. a BP(?). In general, evaporate minerals appeared just at the beginning of the Holocene when temperature increased relative to the late glacial, indicating that increase of evaporation proceeding more quickly at higher temperature in the Holocene is far larger than increase of Asian monsoon precipitation.
Keywords: CHAKA SALT LAKE; CLIMATIC CHANGE; MINERAL COMPOSITION; TIBET